Synthesis, crystal structure and Hirshfeld analysis of a novel supramolecular compound [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O - Guzal Nuralieva; Oydinoy Umirzakova; Batirbay Torambetov; Abdusamat Rasulov; Jamshid Ashurov; Shakhnoza Kadirova (Acta Crystallographica Section E: Crystallographic Communications)
A new cobalt complex, bis[tris(aminothiourea)cobalt(III)] bis[2-(carboxymethyl)-2-hydroxybutanedioato]cobalt(II) tetranitrate tetrahydrate, [Co(CH5N3S)3][Co(C6H6O7)2]0.5(NO3)2·2H2O, designated as [Co(tsc)3]2[Co(cit)2](NO3)4·4H2O, was synthesized. Two crystallographically independent cobalt centers are present. In the first, the central metal atom is chelated by three thiosemicarbazide ligands in a bidentate fashion whereas the second, positioned on a crystallographic inversion center, is hexacoordinated by two citrate anions in a distorted octahedral geometry. Additionally, two water molecules and two nitrate anions are present in the asymmetric unit. Hirshfeld surface analysis revealed that the presence of numerous donor and acceptor groups in the complex, which facilitate hydrogen-bonding interactions that contribute significantly to the overall cohesion of the crystal structure.